1999
DOI: 10.1590/s0102-05361999000200008
|View full text |Cite
|
Sign up to set email alerts
|

Adubação fosfatada em tomateiro industrial em solos do Submédio São Francisco

Abstract: Phosphorus fertilisation on processing tomato in soils of the Submédio S. Francisco River Valley.Results of eight field experiments carried out in irrigated areas of the Submédio São Francisco River Valley, Northeast Brazil, from 1988 to 1993, were statistically analysed to evaluate the response of processing tomato (Lycopersicon esculentum, Mill) to phosphorus fertiliser, in soils with different available phosphorus contents by the methods of Mehlich -1 or Bray -1. The analysis showed that in soils where avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…A deficiência de N durante o período de frutificação reduz a produção e altera a coloração dos frutos (GENUNCIO, 2009). O P é exigido em pequenas quantidades durante a fase de florescimento e frutificação, sua deficiência inicia-se com um menor desenvolvimento das plantas, seguido de clorose nas folhas (FARIA et al, 1999). Segundo Alvarenga (2004) a adubação potássica pode aumentar em 30% a produtividade do tomateiro, pois impede a queda e melhora a qualidade comercial dos frutos.…”
Section: Introductionunclassified
“…A deficiência de N durante o período de frutificação reduz a produção e altera a coloração dos frutos (GENUNCIO, 2009). O P é exigido em pequenas quantidades durante a fase de florescimento e frutificação, sua deficiência inicia-se com um menor desenvolvimento das plantas, seguido de clorose nas folhas (FARIA et al, 1999). Segundo Alvarenga (2004) a adubação potássica pode aumentar em 30% a produtividade do tomateiro, pois impede a queda e melhora a qualidade comercial dos frutos.…”
Section: Introductionunclassified
“…Nishimoto et al (1977) observed that P contents in tomato leaves ranged from 3.0 to 5.0 g/kg, when reaching their maximum yield of 95%. Faria et al (1999), evaluated the production of industrial tomatoes with phosphate fertilization in soils with different phosphorus levels; reported that in soils where available P content was equal to or lower than 2 mg.dm -3 , productivity increased (about 191%); however, soils where available P content was equal to 8 mg dm -3 , it only increased 22%. Moreover, soils where available P content was equal to or greater than 14 mg dm -3 , no response was observed.…”
Section: Introductionmentioning
confidence: 99%